Incomplete excisions of extremity soft tissue sarcomas are unaffected by insurance status or distance from a sarcoma center. Issue 7 (4th September 2013) - Alamanda, Vignesh K.; Delisca, Gadini O.; Archer, Kristin R.; Song, Yanna; Schwartz, Herbert S.; Holt, Ginger E.
Abstract Background Soft tissue sarcomas (STS) continue to be excised inappropriately without proper preoperative planning. The reasons for this remain elusive. The role of insurance status and patient distance from sarcoma center in influencing such inappropriate excisions were examined in this study. Methods This retrospective review of a single institution prospective database evaluated 400 patients treated for STS of the extremities between January 2000 and December 2008. Two hundred fifty three patients had a primary excision while 147 patients underwent re‐excision. Wilcoxon rank sum test and either χ2 or Fisher's exact were used to compare variables. Multivariable regression analyses were used to take into account potential confounders and identify variables that affected excision status. Results Tumor size, site, depth, stage, margins, and histology were significantly different between the primary excision and re‐excision groups; P < 0.05. Insurance status and patient distance from the treatment center were not statistically different between the two groups. Large and deep tumors and certain histology types predicted appropriate referral. Conclusions Inappropriate excision of STS is not influenced by patient distance from a sarcoma center or by a patient's insurance status. In this study, tumor size, depth, and certain histology types predicted the appropriate referral of a STS to a sarcoma center. J. Surg. Oncol. 2013; 108:477–480. © 2013 Wiley Periodicals, Inc.